2005
DOI: 10.4049/jimmunol.175.4.2643
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Peripheral Tolerance following Intracameral Inoculation Are Independent of IL-13 or STAT6

Abstract: The peripheral tolerance that is elicited by the anterior chamber-associated immune deviation (ACAID) protocol is characterized by impairment of Th1 responses such as delayed-type hypersensitivity. It has been proposed that suppression of Th1 responses is mediated by a deviation toward Th2 responses. Because NKT cells have a prominent role in ACAID and NKT cell-derived IL-13 is required in a tumor model of tolerance, we postulated that NKT cell-derived Th2 cytokines might have a role in ACAID. However, contrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…+ suppressor cell in ACAID. It has been shown that ACAID is a phenomenon mediated or maintained by generating an active regulatory T cell population to suppress DTH [15]. Regulatory CD4 + T cells are one of the suppressive populations responsible for the development of ACAID [2].…”
Section: Discussionmentioning
confidence: 99%
“…+ suppressor cell in ACAID. It has been shown that ACAID is a phenomenon mediated or maintained by generating an active regulatory T cell population to suppress DTH [15]. Regulatory CD4 + T cells are one of the suppressive populations responsible for the development of ACAID [2].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the splenic cells of these mice secreted only TGF-␤ when stimulated with OVA in vitro. Furthermore, mice deficient in IL-4/IL-13 and STAT6 genes that are critical for Th2 development readily acquired ACAID suppression after intracameral inoculation of antigens [52]. Finally, the ability of ACAID and ACAID-tolerogenic APCs to suppress Th2-mediated pathogenesis adds the additional evidence to put the notion that ACAID is similar to a Th2 response to rest.…”
Section: The Th2-mediated Asthma Modelmentioning
confidence: 99%
“…More recently, it has been clearly shown that at least the development of the CD8ϩ efferent T reg cell is not dependent on a Th2 response [52]. Thus the question arose as to whether the efferent CD8ϩ T reg cell might suppress Th2 responses, as well as Th1.…”
Section: The Th2-mediated Asthma Modelmentioning
confidence: 99%
“…CD8 + Treg cells also perform their suppressive effect controlling a variety of immune responses, such as intestinal immunity, autoimmunity, oral tolerance, and in prevention of graft versus-host disease [29,30]. Interestingly, ACAID can be induced in IL-4, IL-13, or STAT6 knockout mice [31], indicating that Th2 and related cytokines are independent of CD8 + Treg-mediated immune suppression. Therefore, we propose that ␣GalCer mediates a similar mechanism in preventing T1D in NOD mice, since the suppression effect is also independent of STAT6 [23].…”
Section: Introductionmentioning
confidence: 97%